Assessment of geographical origin and production period of royal jelly by NMR metabolomics - Pierluigi Mazzei; Alessandro Piccolo; Marianna Brescia; Emilio Caprio (Chemical and Biological Technologies in Agriculture, 2020)
Abstract Background Royal jelly (RJ) represents the most valuable product of beekeeping activities. The illegal introduction of RJ of uncertain quality/origin in European agrofood markets is not controlled, since the conventional analytical methods cannot unambiguously distinguish foreign from autochthonous RJ products. Here, we applied liquid-state NMR spectroscopy combined with chemometry to characterize the metabolic profile of representative Italian high-quality RJ products and evaluate the discrimination capacity of this analytical technique. Materials and methods RJ samples were supplied by an Italian consortium of royal jellies producers and developed in the period May–July 2016. Samples were dissolved in a deuterated water solution brought at pH 7.3 and analysed through high resolution liquid-state NMR spectroscopy. 1D and 2D homo- and heteronuclear experiments were acquired to identify the RJ metabolomics profile. Proton NMR spectra were elaborated to conduct an NMR-based metabolomic approach based on PCA and DA chemometric analyses. Results The NMR-based metabolomics precisely and significantly (p value < 0.05, according to Benjamini-Hochberg’s test) authenticated the RJ products, by reliably tracing both their geographical and botanical origin, as well as their production period. In particular, Chinese RJ products exhibited a larger amount of citrate and lysine, accompanied by a lower content of 10-HDA. Our results showed that NMR spectroscopy can recognize low-quality fraudulent products and become an useful analytical tool to certify and trace the RJ molecular composition. Conclusions The application of NMR spectroscopy promises to enable the efficient protection of both the producers and consumers of high-quality royal jelly. In addition, the proposed method may be used in combination with the conventional melissopalynological methods for recognizing frauds.